A one-pot, three-step process for the diastereoselective synthesis of aminobicyclo[4.3.0]nonanes using consecutive palladium(ii)- and ruthenium(ii)-catalysis. Issue 12 (2nd March 2016) - Mostafa, Mohamed A. B.; Grafton, Mark. W.; Wilson, Claire; Sutherland, Andrew
Abstract : A one-pot multi-step process that uses both Pd(ii )- and Ru(ii )-catalysis has been developed for the diastereoselective synthesis of aminobicyclo[4.3.0]nonanes. Abstract : A diastereoselective synthesis of highly substituted aminobicyclo[4.3.0]nonanes has been attained using a one-pot multi-bond forming process. A four-step synthetic route was developed for the efficient synthesis of a series of C-7 substituted hept-2-en-6-yn-1-ols. These compounds were then investigated as substrates for a one-pot, three-step tandem process involving a palladium(ii )-catalysed Overman rearrangement, a ruthenium(ii )-catalysed ring closing enyne metathesis reaction followed by a hydrogen bond directed Diels–Alder reaction. The optimisation of the one-pot process has allowed the rapid preparation of a library of aminobicyclo[4.3.0]nonanes with significant molecular complexity and up to four stereogenic centres.